Anterior Loop of the Mental Nerve- Unlooping its Importance in Dentistry - Issrani, Rakhi; Prabhu, Namdeo; Srinivasan, Arunpriya; Alam, Mohammad Khursheed (Bangladesh Journal of Medical Science, 2019)
In any surgical procedure, proper consideration to anatomical structures along with their precise position is of utmost importance. One such anatomical region in anterior mandible is anterior loop of mental nerve. The dental procedure carried out in anterior mandible can lead to neurosensory disturbances if this loop is injured. The presence of anterior loop have been made using conventional imaging modalities like panoramic and periapical radiography, however, limitations of two-dimensional imaging results in either over- or underestimation of the actual size making its use restricted. Cone Beam Computed Tomography is a gold standard threedimensional imaging modality that allows generating multi-planar slices of an area of interest; its accuracy for analysis and linear measurements of craniofacial structures have been confirmed by several studies. This paper highlights the role of accurate and thorough assessment of the inter-foraminal region and anterior loop of the mental nerve prior to any surgical procedure especially in anterior mandible to avert any neurological complications. Bangladesh Journal of Medical Science Vol.18(4) 2019 p.689-695